Iridoid and phenylethanoid glycosides from Heterophragma sulfureum. (June 2015) - Kaewkongpan, Choosak; Sahakitpichan, Poolsak; Ruchirawat, Somsak; Kanchanapoom, Tripetch
Graphical abstract: An unusual iridoid diglycoside, specioside 6′- O -α-d -galactopyranoside and a new phenylethanoid triglycoside, heterophragmoside were isolated from Heterophragma sulfureum. Highlights: An iridoid glycoside with α-d -galactopyranose was isolated from Heterophragma sulfureum . A new phenylethanoid glycoside was isolated from H. sulfureum . This is the first phytochemical study on H. sulfureum . Abstract: An unusual iridoid diglycoside (specioside 6′- O -α-d -galactopyranoside) and a new phenylethanoid triglycoside (heterophragmoside) were isolated from the leaves and branches of Heterophragma sulfureum together with specioside, verminoside, 6- trans -feruloylcatapol, stereospermoside, (−)-lyoniresinol 3α- O -β-d -glucopyranoside, (+)-lyoniresinol 3α- O -β-d -glucopyranoside, (−)-5′-methoxyisolariciresinol 3α- O -β-d -glucopyranoside, (+)-5′-methoxyisolariciresinol 3α- O -β-d -glucopyranoside, and dehydroconiferyl 4- O -β-d -glucopyranoside. The structural elucidations were based on analyses of chemical and spectroscopic data.